PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NHT(NUMBERED HEAD TOGETHER) (PTK pada Siswa Kelas VII D SMP Negeri 2 Sawit Boyolali Tahun 2014/ 2015) - Sherly Yanti, Ayu, Drs. Slamet HW, M.Pd (2015)
The purposes of this research is to increasing the liveliness and the result of the study in mathematic learning through cooperative learning model of NHT (Numbered Head Together) for VII D grade students in SMP Negeri 2 Sawit. The methods of collecting data are using observation, evaluation, field note and documentation. The techniques of analyzing data are using reduction data, presenting data and conclusion drawing/verification. The result of this research is an increase in liveliness that can be seen from the indicator, there are: 1) the courage of the student to ask the teacher is 36,67%, after the action of cycle II 80%, 2) the courage of the students to answer a question from the teacher 10%, after the action of cycle II 70%, 3) the courage of students to solve a problem in front of the class 30%, after the action of cycle II 83,33%, 4) students that participate in learning process 23,33%, after action cycle II 63,33%. An increase of the result of mathematic learning can be seen from students indicator that passed KKM≥70 33,33%, after the action of cycle II 76,67%.Based on the result above that applying the cooperative learning model of NHT can increasing the liveliness and the result of the mathematic learning of the students.